L-asparaginase purification through silica-based supported ionic liquid-like phase materials - Nunes, João C. F. (2022)
L-asparaginase (ASNase) is an aminohydrolase enzyme widely applied as an anticancer biopharmaceutical in the treatment of lymphoproliferative disorders, as an acrylamide reduction agent in starch-rich foods cooked at high temperatures, and as a biosensor for the detection and monitoring of L-asparagine levels. While extensively distributed in nature, most commercial ASNase are from recombinant microorganisms, whose production can be performed through fermentation. Nevertheless, ASNase downstream processing accounts for up to 80% of total production cost. Hence, the development of a cost-effective downstream process is of emerging concern to allow its widespread use. This work aims the development of a cost-effective purification process for ASNase from complex recombinant Bacillus subtilis cell lysate obtained through ultrasound sonication. Silica-based supported ionic liquid-like phase (SSILLP) materials, previously used to produce ASNase-SSILLP bioconjugates through simple adsorption of commercial ASNase, were investigated as cost-effective ASNase purification supports through a simple adsorption method. The optimization of specific experimental conditions, e.g., medium pH and solid/liquid ratio, was performed through Response Surface Methodology regarding ASNase purity. Through this strategy, process costs, energy consumption, and waste produced, might be significantly reduced, leading to the decrease of ASNase price, thereby enabling its wider application.